Productivity vs security: mitigating conflicting goals in organizations. (12th June 2017) - Mayer, Peter; Gerber, Nina; McDermott, Ronja; Volkamer, Melanie; Vogt, Joachim
Abstract : Purpose: This paper aims to contribute to the understanding of goal setting in organizations, especially regarding the mitigation of conflicting productivity and security goals. Design/methodology/approach: This paper describes the results of a survey with 200 German employees regarding the effects of goal setting on employees' security compliance. Based on the survey results, a concept for setting information security goals in organizations building on actionable behavioral recommendations from information security awareness materials is developed. This concept was evaluated in three small- to medium-sized organizations (SMEs) with overall 90 employees. Findings: The survey results revealed that the presence of rewards for productivity goal achievement is strongly associated with a decrease in security compliance. The evaluation of the goal setting concept indicates that setting their own information security goals is welcomed by employees. Research limitations/implications: Both studies rely on self-reported data and are, therefore, likely to contain some kind of bias. Practical implications: Goal setting in organizations has to accommodate for situations, where productivity goals constrain security policy compliance. Introducing the proposed goal setting concept based on relevant actionable behavioral recommendations can help mitigate issues in such situations. Originality/value: This work furthers the understanding of the factors affecting employee security compliance. Furthermore, the proposed concept can help maximizing the positive effects of goal setting in organizations by mitigating the negative effects through the introduction of meaningful and actionable information security goals.